Survival and Metabolic Modulation of Swimming Crab Portunus trituberculatus During Live Transport - Shi, Ce; Ye, Yangfang; Pei, Feng; Mu, Changkao; Wang, Chunlin (Frontiers in Marine Science, 2021)
Demand from consumers for small quantities of live swimming crab Portunus trituberculatus is rising with the development of e-commerce. However, it is challenging to keep P. trituberculatus alive post-capture. In this study, a transport bag containing oxygen and seawater (24 ppt) was used to investigate the survival and metabolic changes of P. trituberculatus during transport. The results showed that more than 80% P. trituberculatus could survive at least 24 h in the transport bag. The ability of the crabs to survive may be attributed to adaptive metabolism, as suggested by the switch from an aerobic to an anaerobic pathway for energy generation and a decline in amino acid metabolism, nucleic acid metabolism, and osmoregulation. Our findings suggest that the transport bag could effectively extend the post-capture survival time of P. trituberculatus. Metabolic adaptation—especially energy homeostasis—is crucial for crab survival during transport. Our study provides a promising method for the transport of live P. trituberculatus.